The value of caries preventive care among 19-year olds using the contingent valuation method within a cost–benefit approach - Oscarson N, Lindholm L, and Ka¨llesta° l C. (Blackwell Synergy, 2007)
The aim of this study was to explore adolescents with high and no caries experience and their preferences for caries preventive dental care.